Draft Third Five Year Plan 1961-66 (Volume I )Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1961)
There was no integrated First Five Year Plan for the Andaman and Nicobar Islands. Only two schemes were taken up - the Colonisation Scheme and the Road Scheme.
Andaman and Nicobar Administration
Andaman and Nicobar Administration